Islamic Education-Based Entrepreneurship as a Catalyst for Student Business Motivation - Suhendi, Saca; Purnama, Ega Moh. (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
One crucial factor in promoting entrepreneurship within a country is the role of universities through the implementation of entrepreneurship education. This form of education not only offers a theoretical foundation in entrepreneurial concepts but also shapes students' attitudes, mindsets, and perspectives towards starting businesses. This research seeks to understand the concept and implementation of entrepreneurship education in university courses aimed at fostering students’ entrepreneurial interests, the factors that drive this interest, and the advantages of entrepreneurship education. Using qualitative methods with a phenomenological approach, the study gathered data from purposively selected participants through observations, interviews, and documentation. Data validity was ensured through triangulation techniques. Findings reveal that entrepreneurship education, effectively integrated into university courses, significantly boosts students' interest in entrepreneurship. Besides theoretical insights, students gain practical experiences that enhance essential skills, such as marketing, business management, and performance evaluation. Factors influencing entrepreneurial interest include personal ambition, supportive educational environments, and firsthand experiences in business activities. The benefits of these courses include increasing students’ motivation, skills, and preparedness for the business world, along with contributing positively to the country's economic development by nurturing a new generation of entrepreneurs. Salah satu faktor penting dalam pertumbuhan kewirausahaan di suatu negara adalah peran perguruan tinggi melalui penyelenggaraan pendidikan kewirausahaan. Pendidikan kewirausahaan tidak hanya memberikan dasar teori tentang konsep wirausaha, tetapi juga berperan dalam membentuk pola pikir, sikap, dan pandangan mahasiswa terhadap wirausaha. Penelitian ini bertujuan untuk mengetahui konsep pendidikan kewirausahaan, implementasinya dalam perkuliahan guna untuk menumbuhkan minat berwirausaha pada mahasiswa, faktor-faktor yang mendorong minat berwirausaha, serta manfaat dari mata kuliah kewirausahaan bagi mahasiswa. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Subjek penelitian dipilih melalui teknik purposive sampling. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, dan dianalisis menggunakan teknik triangulasi untuk menjamin keabsahan data. Hasil dari penelitian ini menunjukkan bahwa pendidikan kewirausahaan telah diintegrasikan secara efektif ke dalam mata kuliah kewirausahaan, yang berperan besar dalam meningkatkan minat mahasiswa terhadap dunia wirausaha. Mahasiswa tidak hanya mendapatkan pengetahuan teoretis, tetapi juga pengalaman praktis yang memperkuat keterampilan mereka dalam bisnis, seperti strategi pemasaran, pengelolaan usaha, dan evaluasi kinerja. Faktor-faktor yang memengaruhi minat berwirausaha meliputi keinginan pribadi, dukungan lingkungan pendidikan, serta pengalaman langsung dalam kegiatan bisnis. Manfaat dari perkuliahan ini antara lain peningkatan motivasi, keterampilan, dan kesiapan mahasiswa untuk menghadapi dunia usaha setelah lulus, serta kontribusi positif terhadap pengembangan perekonomian negara dengan munculnya wirausaha-wirausaha baru.